THE EFFECTIVENESS OF USING DEBATE TECHNIQUE IN TEACHING SPEAKING SKILL - Matheus Ferry Renaldo; Odo Fadloeli (PROJECT (Professional Journal of English Education), 2021)
This research has purpose to prove the effectiveness of using debate in teaching speaking at eighth grade of SMP Bina Mulia Mandiri West Bandung academic year 2019/2020. The method used in this research is Classroom Action Research (CAR) using two cycles explained through planning, implementing, observation, and reflection on every cycle. The outcome of the research proved that there was an improvement on the students’ speaking skill. It could be proved by the result of the test in this research. The Minimum Score that must be gained by students (KKM) of English lesson was 70. The students mean score was 50 at the first pretest, and 65 in the first post test, and in the second post test the mean of the students score was 85. In addition there were 3 students (8.8%) who exceed the minimum score on pre test. There were 9 students at the first pretest (26.47%) who surpassed KKM. There were 31 students at the second pretest (91.18%) who exceed KKM. Then, from the result of observation and interview the students stated positive responses. The students can be more active and improve their confident for uttering their ideas. The writer conclude that debate technique was effective in teaching speaking English. Keywords:  Speaking, CAR, Debate Technique